The hybridized timber skeuomorph: taking the Ling-xiao Bao-dien of the Chih-nan temple designed by Chung-Yueh Li as an example - Nan-Wei Wu (Journal of Asian Architecture and Building Engineering)
The purpose of this paper is to identify hybrid timber skeuomorph on the first empirical work of the Chinese Classical Style architecture carried out by a native Taiwanese architect, Chung-Yueh Li. The proportions, the composition and forms and numbers of tou-kung were therefore analyzed to compare the timber skeuomorph of the Ling-xiao Bao-dien of the Chih-nan Temple, other temple designs of Zu-Nan Hsieh, and early projects in the Chinese Classical Style architecture. The basis of the analysis was the research results on tou-kung published by the Society for Research in Chinese Architecture. The findings showed that the hybridized timber skeuomorph of the Ling-xiao Bao-dien of the Chih-nan Temple could be found both in the physical project and also in its design processes. The hybridity of the project showed the integration of northern tou-kung in the entire arrangement and the form of individual style with southern tou-kung in the proportions. This reflected the hybridity of the design processes: Li dominated the entire arrangement and forms of the project, whilst Hsieh was responsible for the proportions and forms of tou-kung. Study of this hybridization could further reveal the differences, dynamics and diversity of timber skeuomorphy.